ANALISIS POTENSI SUNGAI KAMPUNG BATIK LAWEYAN SEBAGAI UPAYA PENGEMBANGAN PARIWISATA KOTA - RULLY RULLY; BAMBAN YUUWONO (Fakultas Teknik, Universitas Wijayakusuma Purwokerto, 2021)
AbstractThe city of Surakarta as a cultural city has several areas that are unique and have historical heritage requirements, one of these areas is Kampung Batik Laweyan, where there are still many ancient buildings and is one of the oldest batik-producing micro-industrial villages in Surakarta. The development of the batik tradition in Laweyan is supported by the existence of the Bengawan tributaries (Pelemwulung river and Jenes river), making it a source of water and water transportation infrastructure. Analysis of the potential of the Laweyan Batik Village area has been widely developed, but studies on the potential of the Laweyan river from the aspect of urban tourism are still minimal. The discussion guidelines that will be used in this research are: identifying the drainage system around the river, community activities around the river, Law no. 63 of 1993 regarding the benefits of river and river area boundaries, and the potential and tourism activities in urban areas. Recommendations for natural irrigation systems for area development activities should provide protection for river basins so that the riverbanks function optimally. Based on observations in the Kampung Batik Laweyan River Area, the development around the river, the function of the river as a natural irrigation system, was not responded optimally. From the analysis of this research, it is found that the Kampung Batik Laweyan area still has a natural river environment and is still suitable for use as a river border according to Law number 63 of 1993. So that the border area can be used as a tourism activity. Analysis of river potential is based on the concept of conservation and revitalization. An analytical presentation of the Laweyan river resources produces many alternative natural tourism activities. The response that should be done is to take strategic planning steps, pilot activities, monitor and assess through integrated activities with local communities, related agencies, academics and the city government.Keywords: Potential Laweyan river; City tourism AbstrakKota Surakarta sebagai kota budaya memiliki beberapa kawasan yang memiliki keunikan dan syarat akan peninggalan sejarah , salah satu kawasan tersebut adalah Kampung Batik Laweyan, di kampung tersebut masih banyak terdapat bangunan kuno dan merupakan salah satu kampung industri mikro penghasil kerajinan batik tertua di Surakarta. Berkembangnya komoditas tradisi batik di Laweyan didukung oleh keberadaan anak sungai Bengawan (sungai Pelemwulung dan sungai Jenes), menjadikannya sumber air dan prasarana transportasi air. Analisis mengenai potensi kawasan Kampung Batik Laweyan telah banyak dikembangkan, namun kajian mengenai potensi sungai Laweyan dari aspek parwisata kota masih minim diobservasi. Pedoman pembahasan yang akan dipakai pada penelitian ini adalah : mengidentifikasi sistem drainase di sekitar sungai, kegiatan masyarakat di sekitar sungai, Undang-undang No. 63 tahun 1993 tentang manfaat garis sempadan sungai dan daerah sungai, dan potensi dan kegiatan wisata di kawasan perkotaan. Rekomendasi sistem pengairan alami terhadap aktifitas pembangunan kawasan sebaiknya memberi proteksi terhadap daerah aliran sungai agar kawasan tepian sungai berfungsi optimal. Berdasarkan observasi di Kawasan Sungai Kampung Batik Laweyan pembangunan di sekitar sungai tersebut fungsi sungai sebagai sistem pengairan alami tidak direspon secara optimal. Dari analisis penelitian ini diperoleh temuan kawasan Kampung Batik Laweyan masih memiliki lingkungan alami sungai dan masih layak digunakan sebagai sempadan sungai sesuai Undang-undang nomor 63 tahun 1993. Sehingga di kawasan sempadan tersebut dapat di fungsikan sebagai kegiatan pariwisata. Analisis potensi sungai didasarkan atas konsep konservasi dan revitalisasi. Pemaparan analisa dari sumber daya sungai Laweyan menghasilkan banyak alternatif aktifitas wisata alam. Respon yang sebaiknya dilakukan adalah melakukan langkah strategis perencanaan, kegiatan percontohan, memantau dan menilai melalui keterpaduan aktifitas bersama masyarakat setempat, instansi terkait, akademisi dan pemerintah kota. Kata kunci: Potensi sungai Laweyan; Pariwisata kota